2023
DOI: 10.3201/eid2911.230463
|View full text |Cite
|
Sign up to set email alerts
|

Global Phylogeography and Genomic Epidemiology of Carbapenem-Resistant blaOXA-232–Carrying Klebsiella pneumoniae Sequence Type 15 Lineage

Yuye Wu,
Tian Jiang,
Xianhong He
et al.

Abstract: Prevalence of carbapenem-resistant Klebsiella pneumoniae (CRKP) has compromised antimicrobial efficacy against severe infections worldwide. To monitor global spread, we conducted a comprehensive genomic epidemiologic study comparing sequences from 21 bla OXA-232 –carrying CRKP isolates from China with K. pneumoniae sequence type (ST) 15 strains from 68 countries available in GenBank. Phylogenetic and phylogeographic analyses reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“… 21 The most common mechanism underlying carbapenem resistance in CRKP is the production of carbapenemases, including class A carbapenemases (mainly KPC), class B metallo-β-lactamases (MBLs, mainly NDM), and some class D OXA-48-like carbapenemases (mainly OXA-181 and OXA-232). 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 The most common mechanism underlying carbapenem resistance in CRKP is the production of carbapenemases, including class A carbapenemases (mainly KPC), class B metallo-β-lactamases (MBLs, mainly NDM), and some class D OXA-48-like carbapenemases (mainly OXA-181 and OXA-232). 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…21 The most common mechanism underlying carbapenem resistance in CRKP is the production of carbapenemases, including class A carbapenemases (mainly KPC), class B metallo-β-lactamases (MBLs, mainly NDM), and some class D OXA-48-like carbapenemases (mainly OXA-181 and OXA-232). 22,23 Several recent studies have reported CRKPs carrying multiple carbapenemase genes. 24 KPC and NDM belong to different carbapenemase classes.…”
Section: Discussionmentioning
confidence: 99%
“…An alarming trend is the emergence of multidrug-resistant hypervirulent strains, presenting a new and formidable challenge in the battle against this already perilous pathogen. Of particular concern is the convergence of virulence and carbapenem resistance (e.g., the bla KPC-2 gene carried by a pLVPK-like virulence plasmid) in a single K. pneumoniae hybrid plasmid, which is the most worrisome (Kong et al, 2021;Wu et al, 2023b). Phylogenetic analysis of EDhvKp-3 and other 179 ST29 K. pneumonia strains retrieved from the NCBI GenBank database, strain EDhvKp-3 as reference.…”
Section: Discussionmentioning
confidence: 99%
“…Fasttree v2.1.11 infers an approximately-maximum-likelihood phylogenetic tree from these non-recombinant SNPs. The visualization and annotation of phylogenetic trees, along with the identification of antimicrobial resistance genes, sequence type, clonal complex, Spa type, Sccmec type, PVL type and strain metadata, were carried out using the Interactive Tree of Life (iTOL) V6 web server ( Wu et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%